2019
DOI: 10.36469/9725
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness Analysis of Ribociclib plus Letrozole versus Palbociclib plus Letrozole in the United Kingdom

Abstract: Objective: To evaluate the cost-effectiveness of ribociclib plus letrozole versus palbociclib plus letrozole in post-menopausal women with hormone receptor positive (HR+) and human epidermal growth receptor 2 negative (HER2-) advanced breast cancer from a UK payer perspective. Methods: A cohort-based partitioned survival model was developed to evaluate the cost-effectiveness of ribociclib plus letrozole versus palbociclib plus letrozole in post-menopausal women with HR+/HER2- advanced breast cancer over a lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 23 publications
(25 reference statements)
3
22
0
Order By: Relevance
“…After a comprehensive search based on the inclusion and exclusion criteria, a total of 15 articles (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)…”
Section: Results Of Literature Search and Quality Of The Included Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…After a comprehensive search based on the inclusion and exclusion criteria, a total of 15 articles (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)…”
Section: Results Of Literature Search and Quality Of The Included Literaturementioning
confidence: 99%
“…Eight studies were conducted in the United States (18,20,23,(25)(26)(27)(28)(29), 3 in China (24,26,28), and 1 each in Spain (15), the United Kingdom (16), Singapore (19), Canada (17), and Switzerland (21,22). One of the 14 studies did not describe the study perspective (25), 4 s t u d i e s a d o p t e d a h e a l t h s y s t e m p e r s p e c t i v e (15,19,21,22,24), 6 studies used a health insurance payer perspective (17,18,23,26,27,29), 1 study used a society-wide perspective (20), and 2 studies used both a health system perspective and a health insurance payer perspective (16,28). Study types included cost-effectiveness analysis (CEA) and/ or cost-utility analysis (CUA).…”
Section: Basic Features Of the Enrolled Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“… 118 In addition to these findings, a study found that ribociclib plus letrozole resulted in greater cost‐savings than other CDK4/6 inhibitor‐letrozole combination making it a cost‐effective treatment for ER‐positive BC. 119 …”
Section: Cyclin‐dependent Kinase Inhibitors In Metastatic Tnbcmentioning
confidence: 99%